The Autonomy of Community Law - Barents, René (Kluwer Law International The HagueNL, 2004)
Explains what the special nature of Community law amounts to and the theoretical and practical consequences that follow from this intrepretaion. Shows why Community law can be seen as a clear example of a new phenomenon.